The Relationship of Knowledge and Socio Culture of Mothers to Exclusive Breast Feeding in Aid Community Health Center Lebaho Ulaq Village - Jumria Talamma; Tini; Elisa Goretti Sinaga (Formosa Journal of Applied Sciences, 2023)
The best food for a baby's growth is breast milk.. Problems in breastfeeding are socio-cultural factors and knowledge. Transverse Sectional Research. 30 mothers with The age range of the sample's children was from 6-24 months utilizing the method of total sampling. The independent variables are tingkat kesadaran sosiokultural. Variabel yang terikat adalah exclusive breastfeeding. It used knowledge and socio-cultural questionnaire. The Kolmogorov Smirnov test on the variable knowledge of exclusive breastfeeding obtained a ρvalue of 0.001 <0.05 (ρ<α). Meanwhile, the Fisher's Exact test on socio-cultural variables on exclusive breastfeeding obtained a ρvalue of 0.000 <0.05 (ρ<α). When mother's knowledge’s high, motivated to give exclusive breastfeeding. The mother's social culture and degree of knowledge regarding exclusive breastfeeding are related.